2017
DOI: 10.1002/2017ja024601
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Variation of the Lunar Tide in the Equatorial Electrojet

Abstract: The atmospheric lunar tide is one known source of ionospheric variability. The subject received renewed attention as recent studies found a link between stratospheric sudden warmings and amplified lunar tidal perturbations in the equatorial ionosphere. There is increasing evidence from ground observations that the lunar tidal influence on the ionosphere depends on longitude. We use magnetic field measurements from the CHAMP satellite during July 2000 to September 2010 and from the two Swarm satellites during N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 156 publications
2
41
1
Order By: Relevance
“…Qualitatively, the clarity of a TS signature indicates the relative importance of the TS-generating process compared to other driving factors. Yamazaki et al (2017) find significant longitudinal variability in the amplitude of the semidiurnal lunar variation in the EEJ intensity derived from CHAMP and Swarm observations. To be specific, a larger RS M2 corresponds to a clearer TS pattern.…”
Section: Discussionmentioning
confidence: 80%
“…Qualitatively, the clarity of a TS signature indicates the relative importance of the TS-generating process compared to other driving factors. Yamazaki et al (2017) find significant longitudinal variability in the amplitude of the semidiurnal lunar variation in the EEJ intensity derived from CHAMP and Swarm observations. To be specific, a larger RS M2 corresponds to a clearer TS pattern.…”
Section: Discussionmentioning
confidence: 80%
“…The semidiurnal lunar variations in the EEJ intensity derived from the Swarm A and B data during 5 September to 5 October 2019 are presented in the supporting information (Figure S4). It is found that the amplitude of the EEJ semidiurnal lunar variation is 17.7 ± 2.1 mA/m for Swarm A (14:00–17:00 MLT) and 16.6 ± 2.8 mA/m for Swarm B (11:00–14:00 MLT), which is greater than the climatological value of 9.0 ± 0.4 mA/m as reported by Yamazaki et al () for September daytime (08:00–16:00 local solar time) conditions. The phase, which is defined as the lunar time of maximum, is 10.2 ± 0.2 hr for Swarm A and 10.0 ± 0.4 hr for Swarm B, which is in good agreement with the climatological value of 10.0 ± 0.1 hr.…”
Section: Resultsmentioning
confidence: 99%
“…From this perspective the present results are qualitatively consistent with the wavenumber broadening influence of Earth's magnetic field as noted by Yue et al () in the context of the quasi‐2‐day wave. Yamazaki et al () found the major nonmigrating components of M 2 in the EEJ to be s =3, 4 with respect to geographic longitude. Both of these results stand in contrast to TIMED/SABER temperature analyses (Paulino et al, ) and modeling that includes ocean and Earth tide forcing (Vial & Forbes, ), wherein the M 2 tide in the neutral atmosphere is described by zonal wavenumbers s =−3 to +5.…”
Section: Discussionmentioning
confidence: 99%
“…The nonmigrating tides account for zonal asymmetries in the lunar tide. Apart from the dominant SW2, Yamazaki et al () found the major nonmigrating components of M 2 in the EEJ to be SW3 and SW4. Eastward propagating components were not found to play a role in defining the longitude dependence of M 2 in the EEJ.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation